Evaluation of maxillary sinus expansion in children due to maxillary first molar extraction - Elif Sepet; Gamze Eren; Gülsüm Ak; Arzu Pınar Erdem; Tamer Lütfi Erdem; Mustafa Mert Açıkgöz; Sinem Kuru (Istanbul University, 2019)
PurposeThis study is aimed at understanding the effects of maxillary first molar extractionon the expansion of maxillary sinus in children.Subjects and methods119 patients (aged 11-17 years) who had only one extracted maxillary first molarwere included in the study. The superoinferior differences of the sinus floor positionwere measured in both dentate and edentulous sites on panoramic radiographs.The expansion of the maxillary sinus after maxillary first molar extraction wasinvestigated in relation to fixed anatomic structures. The interorbital line (IL) andtwo zygomatic process lines (IZ) were used as a reference. The vertical distancesbetween the IL and the inferior border of the maxillary sinus (IS) in edentulous (ISX)and in dentate sites (IST) were measured. The data was analyzed statistically.ResultsThe amount of maxillary sinus expansion in ISX was statistically significant incomparison to IST (p<0.001). The most prominent sinus expansions were foundin subjects with extractions over six months prior to analysis (p<0.001). A negativecorrelation was detected between the amount of maxillary sinus expansion andIST (r = -0.438, p<0.001). There was a positive correlation between the amount ofmaxillary sinus expansion and IZT (r = 23.8, p< 0.009).ConclusionThis study showed that the extraction of one maxillary first molar resulted in anegligible amount of sinus expansion in children. The results could be attributed tothere being only one tooth extraction and a transferring of functional forces to thearea of the neighboring teeth.